Association of uric acid with the decline in estimated glomerular filtration rate in middle-aged and elderly populations: evidence based on the China Health and Retirement Longitudinal Study - Ying Liang; Ming Lei; Liu Lin; Peijia Liu; Sini Cui; Kaiyuan Hu; Xinning Shao (BMJ Open)
Objective Whether uric acid (UA) has an effect on renal function remains controversial. We aimed to investigate the association between serum UA with the decline in estimated glomerular filtration rate (eGFR) in middle-aged and elderly populations in the China Health and Retirement Longitudinal Study (CHARLS).Design Longitudinal cohort study.Setting This was a second analysis of a public dataset (CHARLS).Participants In this study, 4538 middle-aged and elderly individuals were screened after removing individuals younger than 45 years old, with kidney disease, malignant tumour and missing values.Outcome measures Blood tests were performed both in 2011 and 2015. Decline in eGFR was defined as an eGFR decrease of more than 25% or deterioration of the eGFR stage during the 4-year follow-up period. Logistic models corrected for multiple covariables were used to analyse the association of UA with the decline in eGFR.Results The median (IQR) concentrations of serum UA grouped by quartiles were 3.1 (0.6), 3.9 (0.3), 4.6 (0.4) and 5.7 (1.0) mg/dL, respectively. After multivariable adjustment, the OR of the decline in eGFR was higher for quartile 2 (3.5–<4.2 mg/dL: OR 1.44; 95% CI 1.07 to 1.64; p<0.01), quartile 3 (4.2–<5.0 mg/dL: OR 1.72; 95% CI 1.36 to 2.18; p<0.001) and quartile 4 (≥5.0 mg/dL: OR 2.04; 95% CI 1.58 to 2.63; p<0.001) when compared with quartile 1 (<3.5 mg/dL), and the p value for the trend was <0.001.Conclusions Over a 4-year follow-up period, we found that elevated UA was associated with a decline in eGFR in the middle-aged and elderly individuals with normal renal function.